Efeito de fontes e doses de manganês no desenvolvimento do cultivar TAA Bola Cheia de feijoeiro comum (Phaseolus vulgaris L.) - Belloni, Ana Laura (Universidade Federal de São Carlos, 2016)
One of the main factors for increasing the productivity of common bean (Phaseolus vulgaris L.) is the correct use of fertilizers. However, this important factor of agricultural production has still been neglected by rural producers, mainly regarding the supply of micronutrients. Manganese (Mn) is an essential micronutrient to the synthesis of chlorophyll and its deficiency has a direct influence on the content of soluble non-structural carbohydrates. The aim of this study was to evaluate the supply of Mn for a common bean cultivar from different sources and rates of Mn fertilizers. Plants of common bean, TAA Bola Cheia cultivar, were grown in pots in a greenhouse, following a 3x3+1 factorial design, with 3 sources of Mn [MnSO4 (soil fertilization), Mn chelated by EDTA, and MnCl2 (leaf fertilization)], applied in three dosages [recommended dosage (RD), 0.5 x RD and 2 x RD], in addition to a control treatment. Plants were harvested at 60 days after emergency and evaluated for biometric (stem length, stem diameter, leaf area, total chlorophyll index, number of pods, dry shoot biomass) and nutritional parameters (chemical analysis of plant tissue). The absorption and accumulation of Mn in the leaves depended on the source, as follows: MnCl2 > MnSO4 = Mn EDTA. The supply with Mn EDTA resulted in significantly higher biometric parameters (number of pods, total chlorophyll, leaf area and dry shoot biomass). The source that resulted in the highest leaf content of Mn was MnCl2, whose application of 2.0 x DR caused symptoms of toxicity in plants (> 700 mg kg-1). There was no correlation between Mn rates and chlorophyll levels in the leaves of plants treated with different Mn supplies, but the total chlorophyll indices were significantly higher in plants that received Mn by leaf fertilization, especially at the 2.0 x RD dose, regardless the source. Thus, the ChlorofiLOG was not adequate to assess the nutritional status of plants in relation to the Mn levels.
Effect of sources and rates of manganese on the development of common bean (Phaseolus vulgaris L.), TAA Bola Cheia cultivar
Keywords: Phaseolus vulgaris; Micronutrientes; Clorofila; Micronutrientes; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FERTILIDADE DO SOLO E ADUBACAO